Struktur Modal Dipengaruhi Oleh Beban Pajak, Risiko Bisnis, Dan Struktur Kepemilikan: Studi pada Perusahaan Manufaktur yang Listed di Bursa Efek Indonesia Periode 2009-2012 - Lukiana, Ninik; Hartono, Hartono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2014)
Funding decisions or purchasing is one of the fundamental factors in estabilishing and ensuring the continuity of operations and development activities of the compay. Managers must be able to raise funds both from within / internal and external sources / external companies, both of types of foreigner capital funds and type of equity.The capital structure of a company is influenced by several factors, and in theory the factors that affect the capital structure is difficult to measure, but some empirical researcher aimed to identify the factors that affect to capital structure decisions have been made, both in Indonesian and in some other countries. The purpose of this research isto test capital structure the influence of tax, business risk and ownership structure of partial and simultaneous. This research is a type of correlation studies (correlation research), nature of casuality, the data type of this research is empirical research (empirical research explanatory hypotheses or casual hypotheses.Population in this study is a manufacturing company that listed on the Indonesia Stock Exchange for the period 2009-2012. Sampling was done by using non-probability purposive sampling method with certain criteria. Analysis of test data by means of multiple regression analysis with the classical assumption test, hypothesis testing with the t test and F test result of the testing of the hypothesis, that in partial tax burden and business risk significantly influence capital structure, while the ownership structure has no significant influence effect on the capital structure. But the tax burden variables, business risk and ownership structure significantly and simultaneously influence capital structure.